Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd007859.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Initial arch wires for alignment of crooked teeth with fixed orthodontic braces

Abstract: Analysis 3.4. Comparison 3 0.014 inch superelastic NiTi wire versus 0.015 inch multistrand stainless steel wire, Outcome 4 Pain intensity (VAS (4th day

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…Longer treatment time with steel wires could be attributed to the intervals when steel wires are passive. However, in the Cochrane review of published randomized controlled trials (RCTs) by Wang et al [ 8 ], no difference in the speed of tooth alignment could be shown after using one initial aligning arch wire over another. Authors commented on the general poor quality of the included trials and suggested that the results should be viewed with caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longer treatment time with steel wires could be attributed to the intervals when steel wires are passive. However, in the Cochrane review of published randomized controlled trials (RCTs) by Wang et al [ 8 ], no difference in the speed of tooth alignment could be shown after using one initial aligning arch wire over another. Authors commented on the general poor quality of the included trials and suggested that the results should be viewed with caution.…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review by Riley and Bearn [ 7 ] on clinical trials on aligning arch wires advocated that there is insufficient data to make clear recommendations regarding the most effective arch wire for alignment. In a later Cohrane review by Wang et al [ 8 ], some additional factors, including the amount of root resorption along with tooth movement and the intensity of pain experienced by patients during initial alignment, were evaluated. The authors concluded that there is some evidence to suggest that there is no difference between the speed of tooth alignment or pain experienced by patients when using one initial aligning arch wire over another.…”
Section: Introductionmentioning
confidence: 99%
“…Weniger Bogenwechsel in der Nivellierungsphase verkürzen die Zeit bis zum Einsetzen des Arbeitsbogen[ 6 ] und somit die Gesamtbehandlungszeit. Dabei scheint auch die Wahl des ersten Bogens keinen Einfl uss auf die Geschwindigkeit der Zahnbewegung oder Schmerzempfi nden der Patienten zu haben[ 7 ] . Letztendlich sollte die Verkürzung der Behandlungszeit durch Reduktion der Bogenwechsel und frühzeitigen Einsatz von slotfüllen-den Bögen der berechtigten Forderung nach leichten Kräften[ 8 ] kritisch gegenübergestellt werden.…”
unclassified